2000
DOI: 10.1177/088626000015008001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of the Risk of Marital Sexual Violence in Bangladesh

Abstract: Sexual violence against women has never been new in history. What is new in the developmental literature is the discovery that this kind of act is wrong and has direct impact on women's health. Using data from a nationally representative sample, this article attempts to improve our understanding about the prevalence and determinants of sexual violence within marriage in Bangladesh. Findings reveal that the probability of a woman to be sexually abused increases if she is young and illiterate and hails from a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 18 publications
4
68
0
Order By: Relevance
“…Two studies – one from Bangladesh and one from South Africa – suggested women’s participation in microfinance had no impact on IPV [44,53], while two studies from Bangladesh suggested involvement in microfinance reduced IPV [50,52], with three others suggesting a potential initial increase in women’s experience of IPV, and a reduction in risk over a longer time period [43,45,51]. In contrast, the other four studies suggested involvement in microfinance increased IPV, particularly under specific circumstances, including living in a conservative area [48], being wealthier [46,47,49] and residing in urban areas [49], suggesting a significant role was played by contextual factors.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies – one from Bangladesh and one from South Africa – suggested women’s participation in microfinance had no impact on IPV [44,53], while two studies from Bangladesh suggested involvement in microfinance reduced IPV [50,52], with three others suggesting a potential initial increase in women’s experience of IPV, and a reduction in risk over a longer time period [43,45,51]. In contrast, the other four studies suggested involvement in microfinance increased IPV, particularly under specific circumstances, including living in a conservative area [48], being wealthier [46,47,49] and residing in urban areas [49], suggesting a significant role was played by contextual factors.…”
Section: Resultsmentioning
confidence: 99%
“…Between 10% and 26% of women report being raped by their husband (Finkelhor & Yllo, 1985;Hadi, 2000;Painter & Farrington, 1999;Russell, 1982;Watts, Keough, Ndlovu, & Kwaramba, 1998). In a sample of young adults in a committed sexual relationship, Goetz and Shackelford (2006) found that 7.3% of men admitted to at least one incidence of raping their current partner and that 9.1% of women reported having experienced at least one incidence of rape by their current partner.…”
Section: Risk Of Sperm Competition and Sexual Coercionmentioning
confidence: 99%
“…Koenig et al found a significant negative relationship between age and violence in Jessore but an insignificant difference in Sirajganj, a relatively more conservative area (6). Age of husbands was not associated with violence according to two quantitative studies from the late 1990s (12,20). However, based on qualitative data from a conservative rural area, Bhuiya et al inferred that husbands aged less than 30 years were substantially more likely to beat their wives than husbands aged over 50 years (8).…”
Section: Homicidementioning
confidence: 99%
“…Youth is a risk factor for violence within marriage (5,6,12,20). In Bangladesh, many marriages are arranged for girls when they are in their teens (18).…”
Section: Homicidementioning
confidence: 99%